2012
DOI: 10.1002/maco.201206723
|View full text |Cite
|
Sign up to set email alerts
|

Covercrete with hybrid functions – A novel approach to durable reinforced concrete structures

Abstract: Due to the corrosion of steel in reinforced concrete structures, the concrete with low water–cement ratio (w/c), high cement content, and large cover thickness is conventionally used for prolonging the passivation period of steel. Obviously, this conventional approach to durable concrete structures is at the sacrifice of more CO2 emission and natural resources through consuming higher amount of cement and more constituent materials, which is against sustainability. By placing an economically affordable conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…[34] The acidification has a direct effect on the structure since it consumes calcium hydroxide (CaOH, Portlandite), where an increase in acidity eventually destroys the calcium-silicate-hydrate (CSH) gel by calcium leaching and deteriorates the bond strength between the cementitious substrate and the anode. [35] In accordance with this, the results strongly suggest that the porous zone indicated by the dashed circle in Figure 13a is due to such microstructural changes and also the most likely reason for the increased electrical resistance of the system.…”
Section: Microstructural Characterizationsupporting
confidence: 79%
“…[34] The acidification has a direct effect on the structure since it consumes calcium hydroxide (CaOH, Portlandite), where an increase in acidity eventually destroys the calcium-silicate-hydrate (CSH) gel by calcium leaching and deteriorates the bond strength between the cementitious substrate and the anode. [35] In accordance with this, the results strongly suggest that the porous zone indicated by the dashed circle in Figure 13a is due to such microstructural changes and also the most likely reason for the increased electrical resistance of the system.…”
Section: Microstructural Characterizationsupporting
confidence: 79%
“…In the Pourbaix diagrams, the pH value at the contact surface between solution and carbon is considered as influencing factor of the carbon's stability. However, it does not take the process of acidification at the anode's surface into account, which is a general and commonly reported issue leading to locally strongly acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also been made to combine the reinforcing property together with the anode function [25], [26]. Zhu et al [27] reported stable anode performance in accelerated ICCP tests of CFRP strip in simulated pore solutions.…”
Section: Applications Of Cfrp As Anode Materialsmentioning
confidence: 99%